Memorandum for Collaboration for K@Borneo 2013 (MoC) - The Borneo Post, - (Banjarmasin, Kalimantan Selatan: Hotel Mercure., 2013)
To establish a regional co-operation on developing and sharing of various information on Borneo and to collaborate in identifying, compiling and digitizing of such information -- To provide and conduct training, organize workshops and meetings and sharing of financial implications in realtion thereto.